Pemanfaatan Fenomena Rashdul Qiblat sebagai Metode Akurat Penentuan Arah Kiblat bagi Masyarakat Perkotaan - Faiz Faricha; Abdul Halim (Impact: Jurnal Pengabdian kepada Masyarakat, 2026)
The inaccuracy of the Qibla direction is a serious problem in urban areas due to people's dependence on digital compasses which are vulnerable to magnetic anomalies and low astronomical literacy among urban circles. This study aims to analyze the use of the Rashdul Qibla phenomenon as an accurate method of determining the direction of the qibla for urban communities, measuring the level of accuracy of the method, and identifying deviations in the direction of the qibla in worship buildings in urban environments. The study used a Participatory Action Research (PAR) approach which involved the active participation of mosque takmirs, prayer room administrators, and worshippers in 15 urban locations as collaborative partners throughout the research cycle. Data was collected through direct measurements using an istiwa stick, digital compass, and theodolite; in-depth interviews with key informants; as well as participatory observation and documentation. The results of the study show three main findings. First, the Rashdul Qibla method produces an average deviation of less than 0.5° against the theodolite reference, much more accurate than a digital compass which shows a deviation between 2° to 7°. Second, the level of public understanding of Rashdul Qiblat is very low (85% have never heard of it), but the PAR approach has succeeded in increasing understanding until 92% of participants are able to practice this method independently. Third, from the 15 mosques and prayer rooms measured, it was found that the deviation in the direction of the qibla varied between 2° to 25° with an average of 9.7%, which indicated a systemic error from the construction stage. This study concludes that Rashdul Qibla is a very accurate and practical method of determining the direction of the Qibla for urban communities, and the PAR approach has proven to be effective in increasing the literacy and independence of the community in determining the direction of the Qibla independently.